2003
DOI: 10.1024/0040-5930.60.1.59
|View full text |Cite
|
Sign up to set email alerts
|

Patient self management of oral anticoagulation

Abstract: Self management of oral anticoagulation (OAC) has been demonstrated to improve the quality of oral anticoagulation as assessed by the percentage of INR values within the individual target range. There were tendentially less bleeding and thromboembolic complications in the group with self management of OAC. The capillary INR values of the only available monitor in Switzerland (CoaguChek, Roche Diagnostics, AG) correlated good with venous INR. Thus, self management of OAC may be a valuable alternative to convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…These studies confirmed a high degree of similarity between home tests and clinic tests. 2,3,4 Studies to establish their clinical role were then undertaken.…”
Section: Editorialmentioning
confidence: 99%
“…These studies confirmed a high degree of similarity between home tests and clinic tests. 2,3,4 Studies to establish their clinical role were then undertaken.…”
Section: Editorialmentioning
confidence: 99%